Human biomonitoring of per- and polyfluoroalkyl substances in German blood plasma samples from 1982 to 2019. (December 2020) - Göckener, Bernd; Weber, Till; Rüdel, Heinz; Bücking, Mark; Kolossa-Gehring, Marike
Highlights: A spectrum of 37 PFAS was determined in 100 human plasma samples from 2009 to 2019. The two legacy substances PFOA and PFOS were detected in every plasma sample. A significant portion of total PFOS analytes was present as branched isomers. Trend analysis revealed declining concentrations for PFOA, PFNA, PFHxS and PFOS. The effects of chemical regulation on the study findings are discussed. Abstract: The findings of per- and polyfluoroalkyl substances (PFAS) in humans and the environment all over the world have raised concerns and public awareness for this group of man-made chemicals. In the last three decades, this led to different regulatory restrictions for specific PFAS as well as shifts in the production and usage of these substances. In this study, we analyzed the PFAS levels of 100 human blood plasma samples collected from 2009 to 2019 for the German Environmental Specimen Bank (ESB) to further elucidate the time course of exposure towards this substance group as shown by Schröter-Kermani et al., (2013) with samples from 1982 to 2010. A spectrum of 37 PFAS, including perfluorocarboxylic (PFCA) and –sulfonic acids (PFSA) as well as potential precursors and substitutes like ADONA, GenX or F-53B was analyzed by UHPLC coupled with high-resolution mass spectrometry. Validation was successful for 33 of the substances. The two legacy substances perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) were detected in every sample of the 2009–2019 dataset and showed the highest concentrations with ranges of 0.27–14.0 ng/mL and 1.21–14.1 ng/mL, respectively. A significant portion of total PFOS analytes was present as branched isomers (mean: 34 ± 7%). High detection frequencies of 95% and 82% were also found for perfluorohexane sulfonic acid (PFHxS) and perfluorononanoic acid (PFNA), respectively, but in lower concentrations (PFHxS: <LOQ – 4.62 ng/mL; PFNA: <LOQ – 3.66 ng/mL) than PFOA and PFOS. Besides other PFCA and PFSA only 8:2 fluorotelomer sulfonic acid (8:2 FtS) and N -methyl perfluorooctane sulfonamidoacetic acid were detected in very few samples. In combination with the previous results from 1982 to 2010, declining temporal trends were observed for all PFAS (PFOA, PFNA, PFHxS, and PFOS) frequently detected in the ESB samples. The results of this study indicate a decrease in human exposure to known PFAS in Germany over the last three decades and emphasize the importance of long-term human biomonitoring studies for investigating the effects of chemical regulation.